2006
DOI: 10.1136/ip.2006.013177
|View full text |Cite
|
Sign up to set email alerts
|

Drinking, drugs and driving in Ireland: more evidence for action

Abstract: Objective: To examine the prevalence of drug positivity among drivers suspected of driving under the influence of an intoxicant, and consequently apprehended by the police in Ireland. Design: 2000 specimens were selected for drug analysis, 1000 with results under the limit for alcohol and 1000 over the limit. The limit for alcohol is 80 mg/100 ml in blood and 107 mg/100 ml in urine. Seven drugs/drug classes were examined; amphetamines, methamphetamines, benzodiazapines, cannabinoids, cocaine, opiates and metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…driving suspects had taken cocaine before driving [49]. A Norwegian road-side study reported that cocaine or its metabolite benzoylecgonine was found in 0.12% of drivers [19], comparable to 1% found in Irish drivers [50]. These studies and others [51], show that the prevalence of cocaineusing drivers differs between studies, ranging from less than 1% to 13%.…”
Section: Cocainementioning
confidence: 83%
“…driving suspects had taken cocaine before driving [49]. A Norwegian road-side study reported that cocaine or its metabolite benzoylecgonine was found in 0.12% of drivers [19], comparable to 1% found in Irish drivers [50]. These studies and others [51], show that the prevalence of cocaineusing drivers differs between studies, ranging from less than 1% to 13%.…”
Section: Cocainementioning
confidence: 83%
“…A Norwegian study found demographic differences between users of prescribed benzodiazepines and apprehended drivers tested positive for benzodiazepines (3). Studies of apprehended drivers from countries outside Scandinavia found a lower prevalence of benzodiazepines varying from 4% in Ireland (20) and Hungary (21) to 6% in Switzerland (22). A study from Finland found benzodiazepines as the most prevalent drug group (76%) in a study of all apprehended drivers from 1977 to 2001 (16).…”
Section: Benzodiazepinesmentioning
confidence: 99%